KAJIAN NILAI-NILAI BUDAYA JAWA DALAM TRADISI BANCAAAN WETON DI KOTA SURAKARTA (Sebuah Kajian Simbolisme dalam Budaya Jawa) - Sukmawan Wisnu Pradanta; Bani Sudardi; Slamet Subiyantoro (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This study investigates symbols on tradition ritual to commemorate the day of birth or bancaan weton in Javanese tradition. Symbols are associated with daily practices for moral and social contexts. This study used ethnography with phenomenological setting for the data collection.  Qualitative approach was used to analyze the data.  The study assigned informants from Kasunanan Surakarta, Mangkunegaran, traditional chief, ulama, and culture practitioners.  The study discovers that bancaan weton symbolizes harmony, tolerance, and implementation of moral, social, spiritual and religious valaues.  In abstract form, values of bancaan weton originate from Javanese Moral Teaching and spiritual philosophy of conducting harmony and balance between the man and God the Almigthy.  The tradition squarely undertakes genuine teaching values of Javanese, however, the existence may dilute as pride to prevent the tradition by Javanese themselves may lax.